(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the study of such a social category as mediation. The relevance of introducing such a procedure in the student community is proved, since the unification of different personalities can become the basis for the development of conflicts. The results of a psychological and pedagogical experiment in two age groups are described: first-year students of various higher educational institutions. It is shown that more often, depending on the age group, students choose a strategy for behavior in a conflict situation as rivalry and cooperation, and the older age group is also a compromise. It is proved that mediation is most effective for resolving conflicts in the student community.